14-3-3σ Protein Expression in Canine Renal Cell Carcinomas. Issue 2 (March 2018) - Suárez-Bonnet, Alejandro; Lara-García, Ana; Stoll, Alexander L.; Carvalho, Sofia; Priestnall, Simon L.
14-3-3σ is a protein expressed in many epithelial tissues associated with essential cell functions, including cell-cycle control, apoptosis, and cytoskeletal integrity. There is a paucity of knowledge of the tumorigenesis of canine renal cell carcinomas (RCCs), and the histological origin of this tumor has not been established. This study analyzed the expression of 14-3-3σ, Ki-67, cytokeratins, and vimentin in 40 canine RCCs. Aberrant expression of 14-3-3σ was demonstrated in 15 (38%) cases and was associated with a significantly shorter survival time ( P < .002). In contrast to canine RCC, normal kidney did not express 14-3-3σ. The Ki-67 proliferation index did not show utility as a prognostic factor. The distal convoluted tubular epithelium in normal kidneys coexpressed cytokeratins and vimentin, and thus maintenance of this coexpression pattern in canine RCC suggests that most tumors arise from the distal segment of the nephron. These results suggest that 14-3-3σ is a potential negative prognostic factor and a possible therapeutic target.